As expressões vivas de corpos idosos frente à queda - Rosa, Ana Elisa Sena Klein da (2012)
The relationship of the body in old age is very particular to each individual. Norbert Elias (2001) discussed the difficulty that our own body, so full of freshness and often pleasant sensations, can be slow, tired and clumsy. We cannot imagine it, and basically we do not want it. The fall followed by femoral fracture causes huge strangeness, an image in which the elder cannot identify himself, resulting in a disconnection between the image of the unconscious of the body and the image that the mirror gives him back. The objective of this study was to delineate the socio-demographic profile of 40 elders (31 females and 9 males) with femur fracture in surgical indication for pre operative phase, attended by the Service of Orthopedics of the Hospital of the State Public Servant of São Paulo (HSPESP). It is a cross-sectional observational study, and the data were collected through visits to files of medical records and semi-structured interviews, during the period of October 2010 to February 2011. All statistical analyzes were performed by SPSS for Windows, version 15.0. The age of the subjects studied ranged from 62 to 97 years old, with an average age equal to 78.9 years old, 77.5% were female, and 72.5% cared by a family caregiver. A factor of extreme relevance was that 97.5% of the subjects use more than 3 concomitant medicines daily. These and many others facts were raised with the intention of cross factors that reflect in the trial of human ageing. For the Gerontology, old age is to be understood by different looks. The social, cultural and subjective aspects permeate and intertwine in old age. With this study was possible to notice that a public health policy is necessary for that the rate of falls can be reduced by taking actions which are intended to give the elderly a better self-awareness of his body, and identify situations that can be harmful in relation to increase the risk of falls